2019
DOI: 10.1073/pnas.1911536116
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for inferring gene relationships from single-cell expression data

Abstract: Several methods were developed to mine gene–gene relationships from expression data. Examples include correlation and mutual information methods for coexpression analysis, clustering and undirected graphical models for functional assignments, and directed graphical models for pathway reconstruction. Using an encoding for gene expression data, followed by deep neural networks analysis, we present a framework that can successfully address all of these diverse tasks. We show that our method, convolutional neural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 43 publications
0
126
0
Order By: Relevance
“…Pioneering work by Iacono et al used single-cell data-derived correlation metrics to generate gene regulatory networks and found that the networks could detect latent regulatory changes 30 . A deep learning approach has also been developed to predict transcription factor targets from single-cell expression data 31 . In this study, we used single cell gene-gene correlations derived after noise regularization to reconstruct a gene network that produced clear immune cell type related modules.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work by Iacono et al used single-cell data-derived correlation metrics to generate gene regulatory networks and found that the networks could detect latent regulatory changes 30 . A deep learning approach has also been developed to predict transcription factor targets from single-cell expression data 31 . In this study, we used single cell gene-gene correlations derived after noise regularization to reconstruct a gene network that produced clear immune cell type related modules.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on a strict peak p-value cutoff to identify binding sites (p value < 10 -400 based on MACS2 (Zhang, et al, 2008)). We next defined a 'promoter region' as 10Kb upstream and 1Kb downstream from the TSS of each gene and assigned TFs to regulate genes if a peak for that TF was identified in the promotor region for the gene as has been previously done (Schulz, et al, 2013;Yuan and Bar-Joseph, 2019).…”
Section: Ground Truth Interactionsmentioning
confidence: 99%
“…The output of all models is a N-dimension (ND) vector, where N depends on specific task on which the TDL is trained (for example, N=1 for interaction predictions and 3 for interaction and causality predictions). The first TDL model we consider is termed 3D CNN and is a direct extension of the 2D CNNC method (Yuan and Bar-Joseph, 2019). In general, 3D CNN consists of one T×8×8 tensor input layer, several intermediate 3D convolutional…”
Section: Architectures For Tdl Modelsmentioning
confidence: 99%
See 2 more Smart Citations